Human development and governance in Africa: Do good fences make good neighbours? - Simplice Asongu; Samba Diop (African Governance and Development Institute (AGDI), 2021)
In this paper, we revisit the relationship between governance and human development in Africa during the period 2010-2019 taking into account the existence of spatial dependence and controlling the endogeneity problem through a Generalized Spatial Two Stage Least Squares (2SLS). The exploratory spatial data analysis reveals the existence of spatial dependence of human development and governance quality. Our empirical findings support that in Africa, "good fences make good neighbours" or proximity matters in the distribution of human development. Implications are discussed.
Keywords: D31; I10; I32; K40; O55; 330; Governance; human development; Africa